The impact of the first 3 years of breast cancer screening on the overall presentation of breast cancer. - Moody, C (1994)
We have assessed the effect of the first round of the Breast Cancer Screening Programme on the presentation of breast cancer in the Southampton Health District with respect to number of cases and pathological characteristics. A retrospective comparative survey of the presentation of breast cancer in the 3 years prior to breast cancer screening (1985-1988) with the presentation of breast cancer during the prevalent round of breast cancer screening (1988-1991) was performed. During the period of study 1536 cases of breast cancer presented. Six hundred and sixty presented in the years prior to screening and 864 during the first round of screening. All patients lived within the Southampton Health District. The study was designed to assess the changes in breast cancer presentation with regard to age, pathological characteristics, and treatment. Even allowing for the increases in the local population there was a significant increase in the number of cases of breast cancer diagnosed (chi 2 = 23.7, df = 1, P < 0.001). The majority of this increase was in the 50-64 age group. There was also a significant shift towards an earlier stage at diagnosis and a significant reduction in tumour size when all cases were included (mean 26 mm versus 34 mm P < 0.001). Screening also created the opportunity for less invasive treatment. Consequently there was a rise in the number of excisions by localization biopsy from 1% to 13% during the screening period. In conclusion, the National Breast Cancer Screening Programme (NBCSP) has had a significant impact on the presentation of breast cancer.(ABSTRACT TRUNCATED AT 250 WORDS)